Evaluating comprehensive carrying capacity of coastal area using the matter-element extension method: A case study in Fujian Province of China. (15th November 2021) - Zhao, Yuning; Xue, Xiongzhi; Huang, Yi; Kong, Hao
Abstract: The acceleration of urbanization and industrialization has placed coastal ecosystems under stress, which influences the sustainable development of coastal areas. As effective carrying capacity is a precondition for coastal sustainability, it is crucial to evaluate coastal carrying capacity by considering coordinated eco-environmental and socio-economic development. However, accurate evaluation is still in the exploratory stage as there is currently no systematic and unified method. In light of this issue, this study applied matter-element extension method, which is appropriate for evaluating multiple factors and complex issues, to evaluate the comprehensive carrying capacity of coastal areas. This research also established a carrying capacity evaluation index system and used the variation coefficient method to determine the weights. Taking the coastal region of Fujian Province as the study area, we assessed the comprehensive carrying capacity for the period from 2011-2018. Carrying capacity status was divided into five grades from Grade Ⅰ (very good) to Grade Ⅴ (very poor). The results showed the grade of each indicator in every research year. They indicated that carrying capacity was Grade III during the study period except when it was Grade Ⅱ in 2016 and 2018. Overall, Fujian's coastal comprehensive carrying capacity was moderate and tended to improve year by year, which meant that the coastal region of Fujian Province was capable of sustainable development and the environment improved as time passed. These results can offer a reference for making coastal management decisions. Furthermore, this approach can provide a novel way to evaluate carrying capacity in other coastal areas. Graphical abstract: The results of the grades of coastal comprehensive carrying capacity in Fujian Province of China from 2011-2018. Image 1 Highlights: Carrying capacity evaluation of coastal area is conducive to coastal sustainability. The matter-element extension method can be used to evaluate carrying capacity of coastal area. The evaluation index system of coastal carrying capacity is based on the carrying object and the carrier. Carrying capacity of Fujian's coastal area was moderate and improved gradually from 2011 to 2018.